Brexit, President Trump, and the Changing Geopolitics of Eastern Europe - Tudoroiu, Theodor (Springer International Publishing, 2018)
This book analyzes the combined consequences of Brexit and of the new US foreign policy under President Trump on the geopolitical situation of Eastern Europe. It perceives the evolution of the East European regional security complex as a struggle between the European Union's Kantian, win-win geopolitical vision and Russia's neoclassical geopolitics, also promoted by President Trump. In the most probable scenario, the latter approach will have the upper hand. The EU's post-Brexit control by the Franco-German axis will likely be followed by the geopolitical irrelevance of the EU due to the renationalization of member states' foreign policy, with Germany becoming the main West European actor. Consequently, Eastern Europe will be turned into the arena of a mainly three-cornered neoclassical geopolitics rivalry opposing Russia, the Franco-German axis and then Germany, and the US in alliance with the post-Brexit UK and certain East European states. The book will appeal to scholars across the fields of International Relations, Geopolitics, European Studies, and Area Studies.